The Roles of Psychological Capital and Gender in University Students’ Entrepreneurial Intentions - Margaça, Clara; Hernández-Sánchez, Brizeida; Sánchez-García, José Carlos; Cardella, Giuseppina Maria (Frontiers in Psychology, 2021)
Universities increasingly play an important role in entrepreneurship, which has contributed to gender equality in the business world. The aim of this study is to establish a causal model of entrepreneurial intentions and explore it by gender, based on the dimensions of the theory of planned behavior, and how these are mediated by the individuals’ resilience and psychological well-being. The previous work experience was considered as one of the control variables, in order to analyze whether this influence the entrepreneurial intention. With a convenience sample of 644 Portuguese students, Structural Equation Modeling (SEM) was used. For a better understanding, multivariate analyzes were performed and each one was individually reported, and for appropriate comparisons by gender, the t-student test was used. The comparison of means, between genders, showed that there are differences only between PBC, SN and EI, with women scoring the highest values, and psychological well-being, with men scoring the higher. A serial mediation path was performed and psychological resilience was found to mediate a significant effect between perceived behavioral control and intention in females, but not in males. It also mediates a significant effect between attitude and intention in females, but not in males. These results show that attitude is a determining factor for females to become entrepreneurs. Finally, after discussing the results, theoretical and practical contributions are analyzed, with regard to the field of entrepreneurship in Portugal, and alternatives are pointed out for a more entrepreneurial future, reinforcing the role of higher education institutions.